2018
DOI: 10.1093/jnci/djy109
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Pooled Safety Analysis of Palbociclib in Combination With Endocrine Therapy for HR+/HER2- Advanced Breast Cancer

Abstract: Based on these long-term safety analyses, there is no evidence of specific cumulative or delayed toxicities with palbociclib plus endocrine therapy, supporting the ongoing investigation of palbociclib plus endocrine therapy in early breast cancer (NCT02513394).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 21 publications
8
65
0
2
Order By: Relevance
“…6 A pooled safety analysis conducted across all PALOMA studies demonstrated that grade 3/4 AST and ALT elevations occurred in 3.3% and 2.3% of palbociclibtreated patients, respectively, again highlighting a reported but rare occurrence. 8 The patient described in the present case report started on combination fulvestrant and palbociclib after her disease showed progression on letrozole. She developed an increase in transaminases after completing 3 cycles of palbociclib.…”
Section: Discussionmentioning
confidence: 75%
“…6 A pooled safety analysis conducted across all PALOMA studies demonstrated that grade 3/4 AST and ALT elevations occurred in 3.3% and 2.3% of palbociclibtreated patients, respectively, again highlighting a reported but rare occurrence. 8 The patient described in the present case report started on combination fulvestrant and palbociclib after her disease showed progression on letrozole. She developed an increase in transaminases after completing 3 cycles of palbociclib.…”
Section: Discussionmentioning
confidence: 75%
“…In a pooled, long-term safety analysis of PALOMA-1, PALOMA-2, and PALOMA-3, 36.9% of patients receiving palbociclib for treatment of HR+/HER2− ABC required dose reduction. Most dose reductions occurred during the first 6 months of treatment and were less frequent during subsequent 28-day treatment cycles (C) than during the first 6 months [9]. Neutropenia and leukopenia were the most common adverse events (AEs) that led to dose reductions in patients treated with palbociclib [9].…”
Section: Introductionmentioning
confidence: 99%
“…Most dose reductions occurred during the first 6 months of treatment and were less frequent during subsequent 28-day treatment cycles (C) than during the first 6 months [9]. Neutropenia and leukopenia were the most common adverse events (AEs) that led to dose reductions in patients treated with palbociclib [9]. The incidence of hematologic and nonhematologic AEs was highest within the first 2 months of palbociclib treatment, which coincided with the period with the most dose modifications (C1-C3) [9].…”
Section: Introductionmentioning
confidence: 99%
“…• Приостановить прием до уровня ≥1,0 х 10 9 /л • Возобновить прием со снижением дозы на 1 уровень • При развитии фебрильной нейтропении* приостановить прием до уровня ≥1,0 х 10 9 /л • В случае повторного возникновения -отмена препарата [24]. В объединенном анализе всех исследований PALOMA по безопасности палбоциклиба 3/4 степень АлАТ и АсАТ наблюдалась у 3,3% и 2,3% соответственно [50]. В 1 случае у пациента с прогрессированием метастазов в печени была документирована печеночная недостаточность [20].…”
Section: рисунок 3 циклин D-cdk4/6 Rb сигнальный путьunclassified